1997
DOI: 10.1023/a:1008206329583
|View full text |Cite
|
Sign up to set email alerts
|

Initial chemotherapy for primary resectable large-cell lymphoma of the stomach

Abstract: Up-front chemotherapy as initial treatment for primary gastric large-cell lymphoma appears to be a safe and effective treatment by which most patients can probably be spared surgical gastrectomy. Consolidation radiation therapy on the stomach can probably improve on the effectiveness of chemotherapy alone. More experience is needed to elucidate the prognostic factors, treatment-related long-term toxic effects and the feasibility of such a treatment administered outside of highly specialized institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…There has been no report of serious adverse effects such as bleeding or perforation in chemotherapy-treated patients of intermediate and high grade non-Hodgkin lymphomas [60] . In a report from Italy, 17 patients with resectable large cell lymphoma treated primarily by chemotherapy with or without consolidation radiotherapy, only two failed in the first line therapy and 15 were free of disease at 6 years [66] . Consolidation radiotherapy might improve the efficacy of chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…There has been no report of serious adverse effects such as bleeding or perforation in chemotherapy-treated patients of intermediate and high grade non-Hodgkin lymphomas [60] . In a report from Italy, 17 patients with resectable large cell lymphoma treated primarily by chemotherapy with or without consolidation radiotherapy, only two failed in the first line therapy and 15 were free of disease at 6 years [66] . Consolidation radiotherapy might improve the efficacy of chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
“…A prospective study from France in 1990 reported a 100% survival in patients with high-grade tumors who underwent resection and adjuvant chemotherapy. A recent series has shown the superiority of combined surgery and chemotherapy to single mode with survival rates between 86%-94% for stages IE and IIE [53,59,66] . In these series the survival rates were higher for those who had complete resection, resection was the most important variable and major determinant of prolonged complete remission [59,60] .…”
Section: Combined Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Small prospective studies with chemotherapy alone or combined with radiotherapy in primary resectable aggressive gastric lymphomas have also been performed (65,66) but definitive conclusions are difficult to draw because the series included few patients and they mixed chemotherapy and radiotherapy.…”
Section: Total Body Irradiation (Tbi)mentioning
confidence: 99%
“…Recently, some have suggested non-operative methods such as H pylori eradication, chemotherapy, or radiotherapy as the primary therapeutic strategies instead of surgery [21,22] . Whereas in our study only 3 patients with remnant tumor in the resection margin undertook radiotherapy, Schecheter et al [23] reported the complete resolution of 17 cases of MALT lymphomas in stages I and II with radiotherapy.…”
Section: Discussionmentioning
confidence: 99%